Structural Analysis of Heat Pump Scroll Compressor for Electric Automobile Air-conditioning - Tang Jingchun; Zuo Chengji (Zhileng xuebao)
In order to solve the problem of heating by electric vehicle air conditioning system in winter, and adapt to the compressor operating characteristics of single stage pressure ratio increasing in winter air condition, therefore, the coefficient of heating performance was decided to be the thermodynamic optimization objective function of scroll compressor. It was determined to the optimal middle pressure of compensation refrigerant in the scroll compressor orifice accordingly. The geometric position and shape of compensation refrigerant orifice have been built, in which has a quasi two-stage compression function. Based on the method of air enthalpy difference, the heat pump type scroll compressor was installed on the electric vehicle air conditioning system, the heating and refrigerating performance experiments had been finished in refrigeration laboratory. By optimized the structure of static scroll plate, the experimental results show that the capability of heating and cooling for the heat pump type electric scroll compressor could be met the comfort requirements of 5 seat electric vehicle drivers and passengers in summer and winter. Furthermore, the performance coefficients of heating and cooling have been improved accordingly. The purpose of energy conservation has been achieved to enhance the automobile air-conditioning system thermal economy of heat pump and refrigeration cycle.